Syntactic and Semantic Analysis on Slogans of Aviation Companies in Asean Countries - Ervina CM Simatupang (English Journal Literacy Utama, 2019)
The title of this study is Syntactic and Sematic Analysis on Slogans of Aviation in Asean Countries. The aim of this study is to analyze and describe the slogans of aviation companies in Asean companies syntactically and semantically. The method used in this study is descriptive method. Data source are taken from official websites of various aviation companies in Asean countries, and there are taken from Wikipedia as the website has listed in chart. The chart has covered the profile of the aviation companies in Asean countries. The theories used to analyze the data syntactically are from O